STUDI PEMANFAATAN ROTAN OLEH MASYARAKAT DI DESA SEKILAP KECAMATAN MANDOR KABUPATEN LANDAK - Roy, Bryan; Fahrizal, .; Diba, Farah (JURNAL HUTAN LESTARI, 2017)
Forest has the potential to meet various human needs such as food, medicine, boards, handicrafts and others. Non timber forest products used by the community in Landak regency are bamboo, rattan, fruit and many kind products. The purpose of research is to describe the types of rattan plants and to describe the benefits of rattan crops in the community of Sekilap village, Mandor district, Landak regency. Methods used in this research survey method to the forest and in-depth interview to the community in Sekilap village. Sekilap village consists of 6 sub village, namely Pangkalatn sub village, Sekilap sub village, Mangke sub village, Buluh sub village, Penawar sub village, dan Baet sub village. The result of the research showed that four rattans used in the community of Sekilap village. The rattan is Rotan Kertong with local name Uwi Tangga Langit (Myrialepis paradoxa), Rotan Taman with local name Uwi Palades (Calamus caesius Blume), Rattan Semambu with local name Uwi Samamok (Calamus scipionum Lour), and Rattan Sega Ayer with the local name Uwi Saga (Calamus axillaris Becc.). Rattan used for craft materials, binding material, basket, bag, chairs, mat, and handcraft. The community used rattan from the forest near their village. Keywords: Calamus axillaris, Calamus caesius, Calamus scipionum, Landak regency, Myrialepis paradoxa, rattan, Sekilap village, The utilization of rattan.